Remodelling baby clinics: Opportunities to support parent–baby relationships. (2nd August 2019) - James, Jessica; Rosan, Camilla
Abstract : This article examines how the 'weigh in' can be a 'way in' to joined-up physical and mental healthcare in baby clinic settings. Instead of a group of parents and babies in a waiting room environment, clinics are remodelled into interactive, playful group community hubs. Pilot projects have taken place and offer evaluation results and practical methods. Professionals work together using their observational skills as a basis for engaging directly with babies and parents, bringing social and emotional development to the fore.